High-performance ocean energy harvesting turbine design – Detailed flow analysis with blade leaning strategy. (May 2019) - Ranjith, B; Halder, Paresh; Samad, Abdus
Oscillating water column wave energy converter is having low efficiency because of its principal component, a bidirectional turbine. An analysis of the internal flow of the turbine gives an idea of improving the performance through optimization of geometrical parameters. In this study, an impulse turbine of 0.3 m diameter with fixed guide vanes is numerically simulated by solving three-dimensional incompressible steady Reynolds averaged Navier-stokes equation with two-equation turbulence closure model. This study shows that the numerical results very well match with the experimental results. The detailed flow physics demonstrates that different types of losses occur in this type of turbine and shows that the downstream diverging path of the rotor and guide vane is responsible for low performance. In this study, the effect of guide vane lean, as well as the combined rotor and guide vane lean on the performance of the turbine, has been discussed in detail and found to increase the efficiency of the turbine.